Mozambique and Angola – The weight of history - Malyn Newitt (Cadernos de Estudos Africanos)
This article examines the political developments in Mozambique and Angola, using the analytical framework constructed by Chabal and Daloz in their book Africa Works. It shows how MPLA and FRELIMO adopted a Marxist-inspired ideology to establish a narrow political elite in power. The text follows the policies pursued by this elite through civil war and the era of the Washington Consensus and shows how it managed to circumvent the conditions which international donors tried to impose. It explains why, after nearly fifty years of independence, Angola and Mozambique remain among the poorest countries in the world while their rulers rank among the richest in Africa.